2011
DOI: 10.1017/s1751731111000978
|View full text |Cite
|
Sign up to set email alerts
|

Traversing the ovine cervix – a challenge for cryopreserved semen and creative science

Abstract: This review brings together research findings on cervical relaxation in the ewe and its pharmacological stimulation for enhancement of the penetration needed for transcervical insemination and embryo transfer. On the basis that the success of artificial insemination is the percentage of ewes lambing, a review is made of recent research aimed at understanding and minimising the sub-lethal effects of freezing and thawing on the viability of spermatozoa, their membrane integrity and their ability to migrate throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 102 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…However, in sheep, <1% of semen is frozen (2), due to extensive structural and functional damage during freezing and thawing reducing sperm quality and fertility (3). Cryopreservation-induced damage to ovine sperm mitochondria reduces energy production and consequently fertility, as the cervix becomes a formidable barrier to sperm transport and sperm have shortened duration of survival in the female reproductive tract (4). However, melatonin protects mitochondria by reducing oxidative stress and preventing mitochondrial permeability transition pore (MPTP) opening (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, in sheep, <1% of semen is frozen (2), due to extensive structural and functional damage during freezing and thawing reducing sperm quality and fertility (3). Cryopreservation-induced damage to ovine sperm mitochondria reduces energy production and consequently fertility, as the cervix becomes a formidable barrier to sperm transport and sperm have shortened duration of survival in the female reproductive tract (4). However, melatonin protects mitochondria by reducing oxidative stress and preventing mitochondrial permeability transition pore (MPTP) opening (5).…”
Section: Introductionmentioning
confidence: 99%
“…There may also be benefi cial components of seminal plasma that are lost when seminal plasma is discarded or diluted during the storage process. Addition of seminal plasma before freezing has been reported to improve sperm survival in the bull, boar, ram, and stallion (Robinson et al 2011 ;Caballero et al 2012 ) and there are reports that addition of seminal plasma after thawing can improve pregnancy rates when ewes are cervically inseminated with frozenthawed semen using the transcervical (Robinson et al 2011 ). Specifi c components of seminal plasma may also interact with sperm cells or in the reproductive tract to enhance pregnancy rates.…”
Section: Semen Preservationmentioning
confidence: 99%
“…1.3 ) that is based on visualization of the os cervix with a lighted speculum, manipulation of the cervix with a forceps, and manipulation of a pipette through the cervix and into the uterus (Buckrell et al 1994 ). Some authors have reported excellent results whereas results were disappointing in other studies (Robinson et al 2011 ). Efforts to improve the system have relied on hormonal regimens to dilate the cervix such as estradiol, prostaglandin E2, and oxytocin (Robinson et al 2011 ).…”
Section: Technologies Focused On Female Reproduction Artificial Insemmentioning
confidence: 99%
See 1 more Smart Citation
“…The tortuous nature of the ovine cervix restricts the transcervical passage of the cannula (Halbert, Dobson, Walton, & Buckrell, ), and many studies have aimed to understand the endocrine mechanism of cervical dilatation in the adult ewe for transcervical cannulation improvement (Robinson et al, ). In prepubertal lambs, there is evidence that both the ability to respond to the steroid hormones of the cervical tissue and the mechanisms for the recruitment of antral follicles and ovulation in response to the administration of eCG are functional (Rawlings, Evans, Honaramooz, & Bartlewski, ; Rodríguez‐Piñón, Meikle, Tasende, Sahlin, & Garófalo, ); however, little is known about the remodelling of the cervical tissue during the prepubertal development of the lambs.…”
Section: Introductionmentioning
confidence: 99%